If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + -12 = 52 Reorder the terms: -12 + 16x = 52 Solving -12 + 16x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 16x = 52 + 12 Combine like terms: -12 + 12 = 0 0 + 16x = 52 + 12 16x = 52 + 12 Combine like terms: 52 + 12 = 64 16x = 64 Divide each side by '16'. x = 4 Simplifying x = 4
| 7(c+1)=4(c-2) | | 7.2+2(3x-2)=133 | | 115x=460 | | 14+3(x+2)=2-2(x+9) | | 7(c+1)=4(c-8) | | 16+5=7x-7 | | (x-6)(2x+4)=(x+8)(x-3) | | 5a-2b=-19 | | 20x=10x-3 | | 7c+7=4c-8 | | -3n(2n-5)=0.5(-12n+30) | | 8-2c=-16 | | .66q+.08=q+.125 | | 20=3X+X | | rt-2n=7 | | 42-21x+12x=144 | | x+3x-4=36 | | 5-(-1+3)=-1+2(-1-3) | | -x+(-3)=8 | | 2z+6+3z=-34 | | 5(x+1)=40 | | 5g=2h-6 | | 2(4x-3)-8-2x=4 | | -9+12+4(3x-3)=7(x-2)-4x+14 | | 2(x-4)-3x=-4(x+2)+3x | | x^4+10x^2-299=0 | | 4y-8-2y=2-(-2) | | -(8(0)+4)=4(0)-2(6(0)+2) | | 4x^2-20xy-7x+35y= | | 3x^2+23x-8= | | 3(x+2)-2=6(x+1)-3x | | 4y-8-27=2-(-2) |